The economic impact of uncertain tourism demand in Hawaii: risk in a computable general equilibrium model - Pratt, Stephen A. (2009)
This thesis estimates the economic impact of uncertain tourism demand in Hawaii. It does this by incorporating risk into a Computable General Equilibrium (CGE) model. CGE models have been used to investigate a wide range of policy issues. To date, none have investigated how uncertainty regarding future tourism demand impacts on an economy.